Evaluating Ice-Temperature Storage Efficacy on Volatile Compounds in Blue Honeysuckle (Lonicera caerulea L.) by Combining GC-IMS and GC-MS - Tianbo Li; Xiaoyu Jia; Jiangkuo Li; Peng Zhang; Dong Qin; Di Wu; Tong Chen; Junwei Huo (Foods)
This study evaluated the efficacy of ice-temperature storage (−1 °C) in preserving volatile compounds (VOCs) in blue honeysuckle (Lonicera caerulea L.) as compared to conventional low-temperature (4 °C) and freezing (−3 °C) storage for 84 d with a 14 d interval. As a flavor-rich berry highly susceptible to postharvest VOC loss, VOC contents and ultrastructural variations were systematically analyzed by coupling gas chromatography–ion mobility spectrometry (GC-IMS), gas chromatography–mass spectrometry (GC-MS), and transmission electron microscopy (TEM). GC-IMS and GC-MS detected 25 and 62 VOCs, respectively, with ice-temperature storage demonstrating well maintaining VOC varieties and relative concentrations. Moreover, TEM analysis further revealed that ice-temperature storage maintained normal cellular ultrastructure integrity, particularly in cell wall organization and organellar morphology. These results conclusively establish ice-temperature storage as the optimal method for preserving both biochemical composition and cytological architecture in blue honeysuckle, thereby providing a scientific foundation for optimizing postharvest protocols and advancing cold-chain technologies for perishable berry fruits.